Studies on Arabidopsis -- Agrobacterium interaction - M. MALLIKARJUNA REDDY, N.P. ESWARA REDDY and (Indian Phytopathology, 2002)
The interaction of Agrobacterium tumefaciens with Arabidopsis thaliana C24 was investigated. A. tumefaciens infection gave a compatible interaction and produced the characteristic tumours. Induction of random beta-glucuronidase (gus) gene fusions intransgenic Arabidopsis after infection with A. tumefaciens was observed. Transgenic Arabidopsis lines At1082 and At1275 had increased GUS expression after infection with A. tumefaciens. A significant increase in GUS activity was observed in line At1082after infection with A. tumefaciens both in shoot cultures and suspension-cultured cells. Histochemical staining results showed that GUS expression was observed in vascular bundles of the leaves mainly above the site of infection. DNA analysis results showed the presence of a single T-DNA copy in transgenic lines At1082 and At1275. Stability experiment results suggested that in line At1082 the T-DNA markers, namely, glucuronidase, nopaline synthase and kanamycin were not stably expressed and had high fluctuations. Genetic analysis results among the progeny of line At1082 suggested that the T-DNA markers segregated independently showing 77% positive for nopaline synthase activity, 36% had GUS expression and 69% had kanamycin resistance. It is suggested that the instability expression of T-DNA markers could possibly be due to DNA methylation.